Regional and District Level Estimates of Maternal Mortality for Nepal: Are they Different from the National Estimates in 2011? - Bhandary, Shital (Journal of General Practice and Emergency Medicine of Nepal, 2014)
Introduction: Nepal won Millennium Development Goal Award on Maternal Health as the Maternal Mortality declined by 50% between 1996 and 2006 and by 80% between 1990 and 2010. However, maternal mortality in Nepal are estimated from Surveys using direct and indirect techniques amid the absence of robust vital registration system. Thus, maternal mortality estimates are not available at regional and district levels. Methods: This paper estimated the regional and district level maternal mortality ratio for 2011 using multilevel regression model coefficients proposed by UN and World Bank for the first time in Nepal. Proportion of Maternal Deaths were estimated using Gross Domestic Product, General Fertility Rate and delivery by Skilled Birth Attendants. The maternal mortality ratio for five development regions and 75 districts were then estimated using the 2011 Census Reports. Results: The maternal mortality ratio at 2011 was estimated as 155 deaths per 100,000 live births and was consistent with the previous values estimated between 1990 and 2010. Maternal mortality at Western and Central development regions were below while Eastern, Mid-Western and Far-Western Regions were above the national estimate. Twenty-two districts had it below while 53 had it above the national estimate. Kalikot and Kaski districts had highest and lowest maternal mortality ratio in 2011. Conclusion: Maternal mortality declined in the country because of rapid fertility decline and increased contraceptive use and decreased anemia among pregnant women and obstetrics/abortion facilities in all districts of the country after legalization of abortion. Improvement in women’s education, empowerment, wealth and living standard were also responsible for declining maternal mortality. Nepal now needs a robust vital registration system to “explain” the reasons of this decline and further devise and implement new plans, policies and programs to reduce it further at sub-national and local levels.